(untitled) (Aporia, 2017)
Genuine modal realism (GMR) holds that whatever is possibile is the case at some possible world and that possible worlds are maximal mereological sums of things that are spatiotemporally interrelated. Metaphysical nihilism (MN) holds that there is a world empty of concrete entities. GMR and MN contradict. A particularly strong argument for MN is the substraction argument (SA). This paper examines to what extent this argument poses a threat to GMR and by which means GMR can possibily be defended. I will lay out two basic strategies to do this and show that both of them face severe problems. Nevertheless, I will point to a prima facie possible way to defend GMR, namely by adopting a claim recently made by E. J. Lowe (2002): some abstract entities exist necessarily and concrete entities are a necessary condition for their existence.